Closed Pig Barn Control System Model - Nattanamaharoj, Nithinan; Tammarugwattana, Narin; Phaisalpanumas, Pipat; Tammaruckwattana, Sirichai (My University, 2024)
This paper presents a temperature and humidity control model for use in a pig barn with an evaporative cooling system and fogging system through an application that can be accessed from the Internet. To be compatible with Farming 4.0 and reduce the problem of epidemics in the pig farm. Temperature and humidity are measured through sensors and used to control them through a microcontroller. Users can monitor the temperature, humidity, and system operation via the application. The control system can be controlled with both manual mode and automatic mode.
Keywords: evaporative cooling system; humidity; temperature